Long-term microclimate monitoring in wildland cultural heritage sites with wireless sensor networks. (1st January 2012) - Xia, Ming; Dong, Yabo; Xu, Wenyuan; Lu, Dongming; Xue, Ping; Liu, Gang
Microclimates in many wildland cultural heritage sites are not under surveillance up to now, due to the lack of power supply and network access. However, real-time microclimate data in cultural heritage sites are very important for research and conservation. In this paper, we discuss the design of a wireless sensor system for long-term microclimate monitoring in wildland cultural heritage sites. Tiered and robust communication architecture including wireless sensor network (WSN), long-distance wireless polling network (LWPN) and internet was developed to realise stable monitoring in complex and harsh environment. Meanwhile, fault detection and diagnosis strategies have been designed to enable quick system restoration once a severe failure occurs. The currently deployed system consists of 241 data sensors covering 57 typical caves of the Mogao Grottoes. The stability and long lifetime of the system are verified through network and battery performance evaluations at the end of the paper.